Measuring The Level Of Perfectionism Among Muslim Gifted And Talented Students - Rosita binti Zainal; Faiqah Atiyyah binti Faridilatras; Puteri Farrah Najeehah binti Megat Nazaruddin; Nursyamilah binti Rosdi; Amnah Zanariah binti Abd Razak (PENERBIT USIM PRESS, 2024)
Abqari Journal. Volume 31 Issue 2 Page (1–9)